The Osgin Gene Family: Underexplored Yet Essential Mediators of Oxidative Stress - Grace Hussey; Marcus Royster; Nivedha Vaidy; Michael Culkin; Margaret S. Saha (Biomolecules)
The Osgin gene family consists of two members, Osgin1 and Osgin2, involved in the cellular oxidative stress response. While many members of this essential cellular pathway have been extensively characterized, the Osgin gene family, despite its broad phylogenetic distribution, has received far less attention. Here, we review published articles and open-source databases to synthesize the current research on the evolutionary history, structure, biochemical and physiological functions, expression patterns, and role in disease of the Osgin gene family. Although Osgin displays broad spatiotemporal expression during development and adulthood, there is ambiguity regarding the cellular functions of the OSGIN proteins. A recent study identified OSGIN-1 as a flavin-dependent monooxygenase, but the biochemical role of OSGIN-2 has not yet been defined. Moreover, while the Osgin genes are implicated as mediators of cell proliferation, apoptosis, and autophagy, these functions have not been connected to the enzymatic classification of OSGIN. Misregulation of Osgin expression has long been associated with various disease states, yet recent analyses highlight the mechanistic role of OSGIN in pathogenesis and disease progression, underscoring the therapeutic potential of targeting OSGIN. In light of these findings, we suggest further avenues of research to advance our understanding of this essential, yet underexplored, gene family.